PERANCANGAN ROOFTOP OFF GRID SOLAR PANEL PADA RUMAH TINGGAL SEBAGAI ALTERNATIF SUMBER ENERGI LISTRIK - Fahmi Hakim, Muhammad (DINAMIKA DOTCOM, 2017)
Electrical energy demand are derived from non-renewable energy is increasing every year. So there is an effort has to be done to reduce or even eliminate dependence on electricity from PLN. One way that is practical and easy is to design offgrid rooftop solar panels on homes. Based on the calculation and design, solar panels are required as many as five panels to power 275 WP, capacity solar charge controller is used at 85 A, it takes four batteries 12 V 230 Ah, teh inverter has power of DC up to 1800 W and output AC power 1500 W maximum, and also the required conductor cross-sectional are 2.5 mm2 with a rating of MCB 16 A.Keywords:renewable energy, solar panel, offgrid